Patients With Schizophrenia and Their Everyday Struggle Through the Jungle of Emotional Cues: A Study About the Theory of Mind in Patients with Schizophrenia - Katrin Lieck (Faculty of Psychology, Universitas Surabaya, 2014)
The theory of mind is the requirement to understand another person’s emotions and thoughts, and to interpret and make predictions about the other person’s intentions based on that understanding. Research on emotions perception on patients with schizophrenia has shown some difficulties for those to identify emotions in facial expressions or conversational prosody, which would suggest an impairment of the theory of mind in patients with schizophrenia. But a deeper look at the results of those studies indicates that patients with schizophrenia do well have the ability to interpret genuine emotional expressions, in contrary to posed expressions. Research has also shown that patients with schizophrenia are very sensitive to negative stimuli. The findings suggest that patients with schizophrenia might not have an impaired theory of mind but rather a different kind of theory of mind or that they just use their theory of mind differently. Teori akal budi (theory of mind) merupakan syarat untuk mengerti emosi dan pikiran orang lain, dan untuk memaknai dan membuat prediksi keinginan orang itu berdasarkan pengertian tersebut. Penelitian tentang persepsi emosi pada para pasien dengan skizofrenia menunjukkan kesulitan mereka mengidentifikasi emosi pada ekspresi wajah atau prosody (pola irama, tekanan, dan intonasi) percakapan, yang menyiratkan suatu kerusakan teori akal budi pada pasien dengan skizofrenia. Namun, hasil pendalaman studi-studi tersebut menunjukkan bahwa para pasien dengan skizofrenia memiliki kemampuan menginterpretasi ekspresi emosional murni, berlawanan terhadap ekspresi yang ditunjukkan. Penelitian juga menunjukkan bahwa pasien dengan skizofrenia sangat sensitif terhadap rangsangan negatif. Temuan juga menyarankan bahwa pasien dengan skizofrenia mungkin teori akal budinya tidak rusak namun hanya berbeda atau mereka hanya menggunakan teori akal budi mereka secara berbeda